A protocol to perform systemic lipopolysacharide (LPS) challenge in rats = Protocolo para realizar reto sistémico con lipopolisacárido (LPS) en ratas - Ramírez Chan, Karol Gabriela 1977-
Lipopolysaccharide (LPS) is a component of the outer membrane of Gram-negative bacteria. In animals, intraperitoneal administration of LPS, stimulates innate immunity and the production of pro-inflammatory cytokines. LPS provides an inflammatory stimulus that activates the neuroimmune and neuroendocrine systems resulting in a set of responses termed sickness behavior. The purpose of this protocol is to describe step-by-step the preparation and procedure of application of intraperitoneal injection of LPS in rats, as a guide for those researchers that want to use this assay to mount an inflammatory response. LPS intraperitoneal challenge in rats has been widely used to evaluate anti-inflammatory reagents and to address basic scientific questions.